THE ROLE OF ENGLISH AS A LINGUA FRANCA IN GLOBAL MARKETING - Masharipova Mohinur Mamur qizi; Hasanova Sitora (TADQIQOTLAR, 2026)
Abstract: In the contemporary globalized economy, English has assumed the role of a lingua franca, functioning as the primary medium of communication in international business and marketing. This article examines how English operates within global marketing practices, focusing on its influence on brand communication, consumer perception, and cross-cultural strategy. Drawing on interdisciplinary perspectives from sociolinguistics, marketing theory, and globalization studies, the paper analyzes both the advantages and the limitations of relying on English as a dominant communicative tool. The findings indicate that while English enhances efficiency, standardization, and global brand identity, its uncritical use may lead to cultural misalignment and reduced local engagement. The study concludes that effective global marketing requires a balanced approach that integrates English with localized linguistic and cultural adaptation.